Spring-assisted cranioplasty for isolated sagittal craniosynostosis: a retrospective review - Jacqueline R Lim; Frederik Fried; Antony Gao; Christopher R Forrest; Damian D Marucci (Australasian Journal of Plastic Surgery)
**Introduction**: Premature fusion of the sagittal suture is the most common form of non-syndromic single-suture craniosynostosis. Surgical correction in infancy is recommended to normalise skull morphology and allow normal brain development, but the optimal approach is controversial. We present our experience with spring-assisted cranioplasty (SAC) for the management of isolated sagittal craniosynostosis.